Membangun Hubungan Dalam Masyarakat: (Telaah Terhadap Ajaran Moderasi Dalam Islam) - Abdulloh Arif Mukhlas (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
Terrorism and radicalism are terms that are closely attached to public understanding. This understanding is not understood in scientific disciplines, but is understood as a crime carried out by some people who follow the Islamic religion. So that terrorism and radicalism are synonymous with Islam. For people who adhere to Islam who are obedient and deep in their religious teachings, they already understand that these actions are actions carried out by some individuals with certain motives and interests, because they know that in the teachings of Islam there is no teaching of violence. But for ordinary people, especially non-Muslims, negative thoughts about Islam will arise or doubt the truth of Islamic teachings as a blessing for the universe. This paper tries to re-examine the basics of social relations in Islam and criticizes some of the inter-religious conflicts that have occurred in some areas in the country.